Penyitaan Kendaraan Bermotor dalam Penegakan Hukum terhadap Balap Liar(Studi pada Unit Gakkum Polres Pringsewu) - Yehezkiel Diko Ardiyansah; Rinaldy Amrullah; Aisyah Muda Cemerlang; Heni Siswanto; Mamanda Syahputra Ginting (CV. ITTC INDONESIA, 2026)
Illegal street racing is a traffic violation that frequently occurs, posing risks to road user safety and public order. Motor vehicle seizure is a law enforcement measure employed by the police to address this violation. This study aims to examine the implementation of motor vehicle seizures involving illegal street racers by the Law Enforcement Unit (Unit Gakkum) of the Pringsewu Resort Police (Polres Pringsewu) and to analyze the factors influencing the effectiveness of this implementation. The study employs both normative-juridical and empirical-juridical approaches, gathering data through literature reviews and interviews with the Head of the Law Enforcement Unit at Polres Pringsewu. The collected data were analyzed using a descriptive-qualitative method. The results indicate that the seizure process has been carried out in accordance with Law Number 22 of 2009 concerning Traffic and Road Transportation and the Criminal Procedure Code (KUHAP). However, the effectiveness of the seizure measures is still constrained by suboptimal criminal sanction regulations, limited personnel and storage facilities for seized items, low public legal awareness, and a persistent culture of illegal street racing among adolescents. These conditions demonstrate that the success of seizure as a law enforcement instrument requires adequate facilities, continuous supervision, and preventive measures to reduce illegal street racing violations within the jurisdiction of Polres Pringsewu.